Should we turn the tent? Inuit women and climate change - Dowsley, Martha; Gearheard, Shari; Johnson, Noor; Inksetter, Jocelyn (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2010)
AbstractMost of the climate change literature for Arctic Canada in the social sciences has focused on men’s knowledge and experiences. Drawing on research from Qikiqtarjuaq and Clyde River, Nunavut, we explore Inuit women’s perspectives on recent environmental changes, many of which are often attributed to climate change by Inuit or others. We divide issues resulting from environmental change into primary and secondary effects. Primary effects are changes in environmental features that affect, for example, hunting, fishing, and travelling. Secondary effects occur in the community as a result of environmental change. These include changes in the use and condition of country products like seal skins, and the psychological and social impact of environmental changes, such as going out on the land less often due to fear of dangerous conditions. We also offer a preliminary discussion on women’s role in responses to climate change, through their often dominant economic and political roles in their communities, the territory, and various wider global governance fora. Our research indicates that gender helps shape Inuit knowledge of environmental change, as well as social responses to perceptions of change. By examining women’s perceptions of environmental change, we draw attention to the social aspects and also highlight how women can contribute to adaptation, not only to physical changes but also to the resulting social changes.